2013
DOI: 10.1371/journal.pone.0059888
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits β-Amyloid-Induced Neuronal Apoptosis through Regulation of SIRT1-ROCK1 Signaling Pathway

Abstract: Alzheimer’s disease (AD) is characterized by the accumulation of β-amyloid peptide (Aβ) and loss of neurons. Recently, a growing body of evidences have indicated that as a herbal compound naturally derived from grapes, resveratrol modulates the pathophysiology of AD, however, with a largely unclear mechanism. Therefore, we aimed to investigate the protection of resveratrol against the neurotoxicity of β-amyloid peptide 25–35 (Aβ25–35) and further explore its underlying mechanism in the present study. PC12 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 48 publications
4
74
0
1
Order By: Relevance
“…No formal assessment has been made in relation to changes in sphingolipid levels in neurons after treatment with resveratrol. Nevertheless, neuroprotection has been consistently observed at <50 µM of resveratrol, which is lower than the concentration required to inhibit SK1 activity (K i = 160 ± 40 μM) and to induce apoptosis (Capiralla et al 2012;Chen et al 2005;Feng et al 2013;Lim et al 2012a;Marambaud et al 2005;Wang et al 2014). Therefore, low micromolar concentrations of resveratrol might mediate protection via a mechanism that does not involve changes in sphingolipid levels.…”
Section: Neurodegenerative Diseasementioning
confidence: 93%
“…No formal assessment has been made in relation to changes in sphingolipid levels in neurons after treatment with resveratrol. Nevertheless, neuroprotection has been consistently observed at <50 µM of resveratrol, which is lower than the concentration required to inhibit SK1 activity (K i = 160 ± 40 μM) and to induce apoptosis (Capiralla et al 2012;Chen et al 2005;Feng et al 2013;Lim et al 2012a;Marambaud et al 2005;Wang et al 2014). Therefore, low micromolar concentrations of resveratrol might mediate protection via a mechanism that does not involve changes in sphingolipid levels.…”
Section: Neurodegenerative Diseasementioning
confidence: 93%
“…For animals used for later EEG recordings, small stainless steel screw electrodes were also fixed in place. Rats were subjected to pilocarpine-induced status epilepticus (SE) 24 h later and euthanized at various time points after antagomir injection (1,3,7,14, and 60 days) for molecular analysis.…”
Section: Intracerebroventricular Injectionsmentioning
confidence: 99%
“…SIRT1 plays a pivotal role in a wide variety of cellular processes such as apoptosis/cell survival, endocrine signaling, chromatin remodeling, and gene transcription. 13 Recent studies have suggested that SIRT1 is an important endogenous apoptosis inhibitor in neurodegenerative disease, 14,15 and several studies have demonstrated that SIRT1 promotes mammalian axon regeneration and supports neurite outgrowth. 16 The miRNA miR199a has been found to target SIRT1 directly.…”
mentioning
confidence: 99%
“…Such effects have been reported in various phenolic compounds: flavones such as baicalein (Caruana et al 2012), flavonols such as Myr, quercetin, and morin (Ono et al 2003(Ono et al , 2006a(Ono et al , 2012Masuda et al 2006;Chakraborty et al 2011;Caruana et al 2012;Ho et al 2013), isoflavones such as glycitein and genistein , flavanols such as EGCG and theaflavins (Ono et al 2003(Ono et al , 2006aLevites et al 2003;Rezai-Zadeh et al 2005;Obregon et al 2006;Bastianetto et al 2006;Ehrnhoefer et al 2008;Bieschke et al 2010;He et al 2011;Grelle et al 2011;Cheng et al 2013;Sinha et al 2012;Rushworth et al 2013;Palhano et al 2013;Lorenzen et al 2014), stilbenes such as resveratrol, nordihydroguaiaretic acid (NDGA), piceid, and viniferin (Ono et al 2002(Ono et al , 2003(Ono et al , 2006a(Ono et al , 2012Savaskan et al 2003;Marambaud et al 2005;Rivière et al 2007Rivière et al , 2009Gauci et al 2011;Capiralla et al 2012;Ge et al 2012;Feng et al 2013;Vingtdeux et al 2010;Caruana et al 2012;Rushworth et al 2013;Richard et al 2013), phenolic acids such as rosmarinic acid (RA), tannic acids (TA), ferulic acid (FA), ellagic aci...…”
Section: Studies Using In Vitro Models Of Cerebral Amyloidosismentioning
confidence: 99%